Phototropic response features for different systematic groups of mesoplankton under adverse environmental conditions. Issue 23 (16th November 2021) - Dyomin, Victor; Morgalev, Yuri; Polovtsev, Igor; Davydova, Alexandra; Morgalev, Sergey; Kirillov, Nikolay; Morgaleva, Tamara; Olshukov, Alexey
Abstract: Current trends in the application of bioindication methods are related to the use of submersible tools that perform real‐time measurements directly in the studied aquatic environment. The methods based on the registration of changes in the behavioral responses of zooplankton, in particular Crustaceans, which make up the vast majority of the biomass in water areas, seem quite promising. However, the multispecies composition of natural planktonic biocenoses poses the need to consider the potential difference in the sensitivity of organisms to pollutants. This paper describes laboratory studies of the phototropic response of plankton to attracting light. The studies were carried out on a model natural community that in equal amounts includes Daphnia magna, Daphnia pulex, and Cyclops vicinus, as well as on the monoculture groups of these species. The phototropic response was initiated by the attracting light with a wavelength of 532 nm close to the local maximum of the reflection spectrum of chlorella microalgae. Standard potassium bichromate was used as the model pollutant. The largest phototropic response value is registered in the assemblage. The concentration growth rate of crustaceans in the illuminated volume was 4.5 ± 0.3 ind (L min) −1 . Of the studied species, the phototropic response was mostly expressed in Daphnia magna (3.7 ± 0.4 ind (L min) −1 ), while in Daphnia pulex, it was reduced to 2.4 ± 0.2 ind (L min) −1, and in Cyclops vicinus, it was very small—0.16 ± 0.02 ind (L min) −1 . This is caused by peculiar trophic behavior of phyto‐ and zoophages. The addition of a pollutant, namely potassium bichromate, caused a decrease in the concentration rate of crustaceans in the attracting light zone, while a dose‐dependent change in phototropic responses was observed in a group of species and the Daphnia magna assemblage. The results of laboratory studies showed high potential of using the phototropic response of zooplankton to monitor the quality of its habitat thus ensuring the early diagnostics of water pollution. Besides, the paper shows the possibility of quantifying the phototropic response of zooplankton using submersible digital holographic cameras (DHC). Abstract : This paper describes laboratory studies of the phototropic response of plankton to attracting light. The studies were carried out on a model natural community that in equal amounts includes Daphnia magna, Daphnia pulex, and Cyclops vicinus, as well as on the monoculture groups of these species. The phototropic response was initiated by the attracting light with a wavelength of 532 nm close to the local maximum of the reflection spectrum of chlorella microalgae. The results of laboratory studies showed high potential of using the phototropic response of zooplankton to monitor the quality of its habitat thus ensuring the early diagnostics of water pollution.